Twiddler Syndrome without Lead Dislodgment Discovered by Remote Monitoring - Catherine Champagne; Nicolas Dognin; Franck Molin; Christian Steinberg; François Philippon; Jean-François Sarrazin; Gilles O'hara; Isabelle Nault; Karine Roy; Benoit Plourde; Louis Blier; Jean Champagne (Case Reports in Cardiology)
Twiddler syndrome is an uncommon yet dangerous phenomenon usually resulting in lead displacement with loss of capture of cardiac implantable electronic devices. In this case report, we present an interesting case of Twiddler syndrome without lead dislodgment which was detected by an alert triggered by an increase in impedance on remote monitoring.